Western Interstate Commission for Higher Education Biennial Legislative Work Conference on Higher Education (9th). On Target Key Issues of Region, State, and Campus - Western Interstate Commission for Higher Education, Boulder, CO.; Lavin, Mary Jo; Western Interstate Commission for Higher Education, Boulder, CO. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
To provide a forum for discussing mutual concerns shared by legislators and educators and more specifically to promote a better understanding and clearer communications between the Western Interstate Commission for Higher Education (WICHE) and state legislators was the purpose of the 1975 Legislative Work Conference attended by 180 western legislators, educators, and government officials. This document contains presentations made at the Conference: the keynote address "Higher Education Issues and the Legislative Process" by Donald R. McNeil; "The Legislative Council of the Southern Regional Education Board: How It Works" by Senator W. E. (Pete) Snelson; "Dollar, Dollar, Who Gets the Dollar?: Making Decisions in a Time of Fiscal Stringency" by Frank M. Bowen; "Demands Across the Table: Trends, Effects, and Issues in Collective Bargaining in Higher Education" by George W. Angell; "The Buck Stops Where?: State Responsibility for Postsecondary Education" by Elizabeth H. Johnson; "How the West Was One: Alternative Means of Providing Access to Postsecondary Education" by Virginia W. Patterson; "I Came Back: Lifelong Learning" by Martha E. Church; "The Unbudget: State Support for Postsecondary Education in Times of Financial Stringency" by George B. Weathersby; "Today, Tomorrow, and the Day After: Higher Education in the 1980s" by Malcolm Moos; "Ivory Tower Dues: Institutional Responsibility to the State, William E. Davis; and "Legislation and the Campus: The Relationship of the Political Process to Postsecondary Education--A Plea for Restraint" by Lee R. Kerchner. (JT)
Educational level discussed: Higher Education.
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Conferences; Educational Finance; Educational Legislation; Educational Problems; Financial Problems; Government Role; Higher Education; Institutional Role; Legislators; Postsecondary Education; Regional Cooperation; State Aid; State Government; State Legislation; Western Interstate Commission for Higher Education; Speeches/Meeting Papers